2022
DOI: 10.1002/nbm.4780
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate‐weighted CEST (gluCEST) imaging for mapping neurometabolism: An update on the state of the art and emerging findings from in vivo applications

Abstract: Glutamate is the primary excitatory neurotransmitter in the mammalian central nervous system. As such, its proper regulation is essential to the healthy function of the human brain, and dysregulation of glutamate metabolism and compartmentalization underlies numerous neurological and neuropsychiatric pathologies. Glutamate‐weighted chemical exchange saturation transfer (gluCEST) MRI is one of the only ways to non‐invasively observe the relative concentration and spatial distribution of glutamate in the human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 83 publications
2
13
0
Order By: Relevance
“…Using a more spatially resolved 2D approach for glutamate quantification based on chemical exchange saturation (GluCEST), Roalf et al ( 26 ) noted an overall decline in glutamate levels in patients with early stage psychosis. The advantage of GluCEST is the ability to quantify regional brain glutamate distribution across multiple cross-sectional whole brain slices in a reasonably short time period ( 27 ), thus promising more extensive studies of glutamate physiology in the near future.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…Using a more spatially resolved 2D approach for glutamate quantification based on chemical exchange saturation (GluCEST), Roalf et al ( 26 ) noted an overall decline in glutamate levels in patients with early stage psychosis. The advantage of GluCEST is the ability to quantify regional brain glutamate distribution across multiple cross-sectional whole brain slices in a reasonably short time period ( 27 ), thus promising more extensive studies of glutamate physiology in the near future.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…It requires both an ultra‐high B 0 field (≥7T) and a high and uniform B 1 + strength across the tissue to generate adequate contrast. As data acquisition has moved from single‐slice (two‐dimensional: 2D) to volumetric slabs (three‐dimensional: 3D), the absolute spread of B 1 + amplitude over the field of view increases and, because one now needs to collect more points in k ‐space per saturation pulse, the minimum B 1 + amplitude required to maintain glutamate derived contrast at an acceptable level increase as well 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…As data acquisition has moved from single-slice (two-dimensional: 2D) to volumetric slabs (three-dimensional: 3D), the absolute spread of B 1 + amplitude over the field of view increases and, because one now needs to collect more points in k-space per saturation pulse, the minimum B 1 + amplitude required to maintain glutamate derived contrast at an acceptable level increase as well. 9,10 One of the primary ways in which B 1 + inhomogeneity has been mitigated recently has been through the use of parallel transmit (PTX). There have been many studies that have used PTX based approaches to correct for B 1 + inhomogeneity, [11][12][13] even in the case of CEST imaging; however, it has not been shown that PTX can maintain a high absolute B 1 + power over the entire field of view.…”
Section: Introductionmentioning
confidence: 99%
“…environments or molecular dynamics, exchange and cross-relaxation rates can vary by several orders of magnitude. This broad scope hints at the potential for using magnetization exchange methods (e.g., CEST, MTC, rNOE) to study a large number of biological systems in situ, including signals from mobile proteins and peptides, [12][13][14][15][16] creatine and phosphocreatine, [17][18][19][20] small sugars and sugar polymers, 10,[21][22][23][24][25][26][27] glutamate, [28][29][30] myo-inositol, 31 urea, 32,33 and glycosaminoglycans, 34 but it can be challenging to separate these multiple signal sources in vivo.…”
mentioning
confidence: 99%